Hormonal protocols for in vitro production of Zebu and taurine embryos - Fernandes, Carlos Antônio de Carvalho; Miyauchi, Tatimara Maria; Figueiredo, Ana Cristina Silva de; Palhão, Miller Pereira; Varago, Fabiana Cristina; Nogueira, Ester Siqueira Caixeta; Neves, Jairo Pereira; Miyauchi, Tochimara Aparecida (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effects of hormonal synchronization protocols, associated or not with follicular development stimulation, on the recovery of oocytes and on in vitro production of Bos indicus and B. taurus embryos, in different seasons. Ultrasound‑guided follicular aspirations (n=237) were performed without pre‑treatment (G1, control group) and after follicular wave synchronization (G2), or after follicular wave synchronization and follicle growth induction (G3). Bos indicus produced more oocytes and embryos than B. taurus (18.7±0.9 vs. 11.9±0.6 oocytes and 4.8±0.3 vs. 2.1±0.2 embryos). On average, oocyte and embryo yields were higher in G3 than in G2, and both were greater than in G1, which lead to a higher conversion of oocytes to embryos in these treatments. The hot or the cold season did not affect the B. indicus outcomes, whereas, in B. taurus, both oocyte recovery and embryo production were higher in the cold season. Follicular wave synchronization improves ovum pick‑up and in vitro production of embryos in both cattle subspecies evaluated.